Kecakapan Managerial, Skema Bonus, Managemen Laba, dan Kinerja Perusahaan - Lilik Purwanti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Earning management is choice to manager in determining policy of accountancy to maximize manager utilitas and improve company value. One of the motivation of earning management is to get bonus that based on profit obtained by manager. Managerial Capability influence manager do earning management. Capable Manager and can make decision which giving added value to company is one of the successfulness key a company. To increase profit or company performance, manager do earning management.Keywords: earning management, Managerial Capability, bonus